2017
DOI: 10.1111/jog.13519
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of uterine myoma after myomectomy: Open myomectomy versus laparoscopic myomectomy

Abstract: AimOpen myomectomy (OM) was previously frequently performed; however, laparoscopic myomectomy (LM) has recently become more common. Nevertheless, myoma can recur after both LM and OM. In this study, we report our retrospective investigation of myoma recurrence by comparing LM and OM.MethodsA total of 474 patients underwent LM and 279 patients underwent OM. The patients were followed‐up postoperatively from six months to eight years. Recurrence was confirmed when a myoma with a diameter of ≥ 1 cm was detected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 16 publications
3
57
0
7
Order By: Relevance
“…It is most often offered to patients who desire future fertility but is also considered by those who have completed childbearing and wish to retain their uterus. Myomectomy provides temporary reduction in uterine volume and improvement of symptoms in up to 80% of women but is associated with an approximately 27% risk of recurrence after removal of a single fibroid, and greater than 50% in the case of multiple fibroids . Myomectomies are overall associated with a low rate of complications (1%–5%) .…”
Section: Managementmentioning
confidence: 99%
“…It is most often offered to patients who desire future fertility but is also considered by those who have completed childbearing and wish to retain their uterus. Myomectomy provides temporary reduction in uterine volume and improvement of symptoms in up to 80% of women but is associated with an approximately 27% risk of recurrence after removal of a single fibroid, and greater than 50% in the case of multiple fibroids . Myomectomies are overall associated with a low rate of complications (1%–5%) .…”
Section: Managementmentioning
confidence: 99%
“…In recent years, LM has been increasingly performed because it is minimally invasive and has lower rate of postoperative intraperitoneal adhesions than OM. However, in our previous retrospective study, we reported that the postoperative recurrence rate after LM was significantly higher than that after OM …”
Section: Discussionmentioning
confidence: 74%
“…For LM, once a uterine manipulator had been inserted, a pneumoperitoneum needle was placed through the umbilicus, and pneumoperitoneum was then achieved by using the closed method . Subsequently, the first trocar was inserted through the umbilicus, followed by the laparoscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations